Kardiale und metabolische Risikofaktoren bei schweren psychischen Erkrankungen: Aufgaben eines Präventionsmanagers = Cardiac and metabolic risk factors in severe mental disorders - Lederbogen, Florian; Bohus, Martin; Deuschle, Michael (Der Nervenarzt, 2015)
People with severe mental disorders have a reduction in life expectancy of 13-30 % compared with the general population. This severe disadvantage is primarily due to an increased prevalence of cardiac and metabolic disorders, especially coronary heart disease (CHD) and type 2 diabetes mellitus and are the result of untoward health behavior characterized by smoking, low levels of physical activity and unhealthy dietary habits. Obesity, arterial hypertension and lipid disorders are also associated with this behavior and further increase the risk of CHD and type 2 diabetes. Thus, people with mental disorders constitute a population with a high risk of cardiovascular events. Appropriate measures for prevention and therapy are urgently indicated but rarely applied. This article presents new organizational structures to overcome this deficit with a prevention manager playing a central role in organizing and applying preventive and therapeutic care. Results from cardiology and diabetic medicine have shown the effectiveness of pooling this responsibility. The measure has the potential to reduce the increased mortality of people with severe mental disorders.